2023
DOI: 10.5826/dpc.1303a168
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Measurements of the Facial Effects of Microdoses of Botulinum Toxin

Doris Hexsel,
Indira Valente-Bezerra,
Gabriela Mosena
et al.

Abstract: Introduction: Studies have suggested that botulinum toxin A may improve skin quality, and application protocols using hyper-diluted doses of botulinum toxin (microdosing) have been studied as a way to achieve therapeutic goals without fully paralyzing the targeted muscles. Objectives: To evaluate the effects of a combined protocol utilizing both the standard dosing and the microdosing of AbobotulinumtoxinA for the improvement of skin quality, measured by objective and subjective measurements. Methods: Thirty p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…11,12 Simultaneously, a clinical survey focusing on BTA adverse reactions in clinical practice proved the adverse reaction of BTA is actually not rare but usually inconspicuous, thus almost having no influence on subsequent treatment procedure and patients' satisfaction. 6 We suspected that most clinicians and patients might ignore some early and inconspicuous BTA hypersensitive reactions in the first place, but the subsequent injection without protective measures could lead to a severe and unexpected consequence and invoke serious medical accidents. According to the literature review, we noticed that the BTA allergic symptoms reported so far all occurred around the injection sites or primarily occurred in the injection sites before spreading to other sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Simultaneously, a clinical survey focusing on BTA adverse reactions in clinical practice proved the adverse reaction of BTA is actually not rare but usually inconspicuous, thus almost having no influence on subsequent treatment procedure and patients' satisfaction. 6 We suspected that most clinicians and patients might ignore some early and inconspicuous BTA hypersensitive reactions in the first place, but the subsequent injection without protective measures could lead to a severe and unexpected consequence and invoke serious medical accidents. According to the literature review, we noticed that the BTA allergic symptoms reported so far all occurred around the injection sites or primarily occurred in the injection sites before spreading to other sites.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The BTA allergic symptoms reported so far all occurred around the injection sites or primarily occurred in the injection sites before spreading to other sites. 6 We have noticed several patients in our clinical practice who experienced inconspicuous and nonpruritic erythema on the chest after BTA injection into the upper face, but the injection sites showed no anomaly. We speculate that some of the BTA we injected may have diffused into the blood and invoked some kind of hypersensitive reaction…”
Section: Introductionmentioning
confidence: 95%
“…(1) Although inactive after two months, longer-term reduction in muscle tension is seen in botulinum toxin's cosmetic and dental uses [35][36][37][38][39]. (2) The botulinum weakens the strong (concave) side of the lumbar curve, enabling the actin and myosin fibers of the weak (convex) side to slide further together, increasing the number of cross bridges, and proportionately increasing their power to contract [40], in addition to the continual strengthening the yoga pose provides during the latter part of the three-month period.…”
Section: Discussionmentioning
confidence: 99%